Reading gender : studies on medieval manuscripts and medievalist movies - Lifshitz, Felice, 1959- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This collection brings together twelve essays published between 1988 and 2014, two of which are here translated into English from (respectively) their original French or German. All the essays use gender as the main category of analysis, whether of late ancient or early medieval texts or of modern medievalist films. The historical studies of medieval Europe emphasize the use of manuscript-level evidence, that is, actual sources from the period in question; arguably, this approach provides a more accurate understanding of the period than does work done on the basis of printed and edited sources. Furthermore, many of the manuscript-based essays specifically exploit liturgical or liturgy-adjacent materials; this is an area of research and a type of manuscript that has rarely been approached through a gendered lens. Meanwhile, the cinematic medievalism essays focus on the processes of remediation and adaptation, searching specifically for points at which filmmaking teams diverged from their sources as evidence for the main goals of the films (while also attending to production contexts and to reception). The juxtaposition in a single collection of scholarship on medieval manuscripts and modern movies illustrates how period specialists can contribute to conversations in the field of (historical) film studies. The book will be of interest to historians of women, gender, Christian liturgy, medieval Europe, medievalism, and historical film"--
Keywords: Literature, Medieval -- History and criticism; Manuscripts, Medieval; Sex role in literature; Historical films -- History and criticism; Middle Ages in motion pictures; Sex role in motion pictures; HISTORY / Medieval